Research and Design of Signal Conditioning Circuits for High Volume Neural Signal Monitoring SoC - Wang, Xingyu (fi=Turun yliopisto|en=University of Turku|, 2016)
With the development of technology, using integrated micro system to monitor neural signals to reach the target application of prevention and treatment of nervous system diseases, such as dementia, epilepsy, Parkinson's disease has become a hot topic in the fields of biomedical sciences and the integrated circuits. The core of this kind of neural signal monitoring micro system is system on chip of high integration and ultra-low power consumption. This thesis is devoted to the research of signal conditioning circuit for high volume neural signal detection system. The key focus is the research of low power filter and amplifier technology, which has very good academic research significance. In this thesis the international advanced progress of the neural signal monitoring system is investigated in detail, and the design requirements of the conditioning circuits for high volume SoC are analyzed. According to the design requirements, the thesis chooses suitable modules to realize the different functions of the conditioning circuit. In this design, the conditioning circuit is realized by a high -pass filter, a low-pass filter and a variable gain amplifier. For each module, this thesis proposes a specific circuit. The transfer function and cutoff frequency is detailed analyzed and trade-off optimization design is done to get better performance in aspects of noise, power and output linearity. The whole circuit is designed under the condition of 1P6M CMOS 0.18um process. The Spectre simulation results of the conditioning circuit and the layout of the low-pass filter are given in the thesis. Simulation results show that the circuit presented band-pass frequency response characteristics. The high-pass cutoff frequency is adjustable in the range of 1Hz~10Hz. The low-pass cutoff frequency is adjustable in the range of 300Hz~10 kHz. The pass-band gain is adjustable in the range of 2dB~40dB. Under the supply voltage of 1.8V, the power consumption is 2.16uW.